POTENSI DAUN SERAI UNTUK MENGENDALIKAN HAMA Callosobruchus analis F. PADA KEDELAI DALAM SIMPANAN - - Herminanto; - Nurtiati; D. M. Kristianti (Universitas Trunojoyo Madura, 2010)
A research has been conducted to know: effects of citronella leaf and serai leaf ash to mortality, numbers of eggs and adults of C. analis emerged on stored soybean seeds; damage and weight reduction of stored soybean seeds attacked by C. analis; and effective doses of the citronella leaves and leaf ash for controlling the pest. The research was carried out in the Laboratory of Plant Pest Faculty of Agriculture Jenderal Soedirman University for four months. It used a factorial randomized complete block design with three replicates. The first factor was citronella leaf doses (control, 2 g/500 g, 4 g/500 g, and 6 g/500 g of soybean seeds). The second one was doses of citronella leaf ash (control, 0.3 g/500 g, and 0.6 g/500 g of soybean seeds). Results of the research performed that combined treatments in the highest leaf and leaf ash doses could increase the mortality of the C. analis adults until 98.99%. Such combined doses were also able to suppress deposited eggs and adult emergence. The highest doses of the citronella leaf and leaf ash in combination decreased seed damage (9.56%) and seed weight reduction (2.4%) of soybean. Effective doses of the citronella leaf and leaf ash for controlling the pest were 6 g/500 g and 0.6 g/500 g of soybean seeds.